Past and Present Energy Societies How Energy Connects Politics, Technologies and Cultures - Möllers, Nina; Zachmann, Karin (Science Studies, 2012)
Abundant, salutary, problematic - energy makes history. As a symbol, resource and consumer good, it shapes technologies, politics, societies and cultural world views. Focussing on a range of energy types, from electricity and oil to bioenergy, this volume analyzes the social, cultural and political concepts and discourses of energy and their implementation and materialization within technical systems, applications, media representations and consumer practice. By examining and connecting production, mediation and consumption aspects from an international and interdisciplinary perspective, the book offers an innovative view on how energy is imagined, discussed, staged and used.